Distinct defensive activity of phenolics and phenylpropanoid pathway genes in different cotton varieties toward chewing pests. (3rd May 2020) - Dixit, Garima; Srivastava, Alka; Rai, Krishan Mohan; Dubey, Rama Shanker; Srivastava, Rakesh; Verma, Praveen Chandra
ABSTRACT: Identifying the maximum level of inherent defense against harmful insects in natural variation among wild lineages of crop plants may result in high yield tolerant varieties and reducing use of chemical insecticides. However, knowledge of natural cotton genotypes with high insect‐resistance is still indistinguishable at the biochemical or molecular level. In the present study, different cultivated Gossypium hirsutum varieties were evaluated for their inherent insect-tolerance against two major cottons chewing pests. The insect bio-assay identified two tolerant and one susceptible cotton varieties. The study demonstrates difference in phenolic acids, proanthocyanidin and tannin accumulation in tolerant and susceptible varieties. The post–infestation of chewing pests increases transcript level of the phenylpropanoid pathway genes were detected in tolerant varieties as compared to the susceptible varieties. Altogether,  chewing pest-tolerance level in cotton varieties is the cumulative effect of enhanced phenylpropanoid pathway genes expression and secondary metabolite leading to defense responses to conventional host plant.